Cost of treating inpatient falciparum malaria on the Thai-Myanmar border - Kyaw, S; Drake, T; Ruangveerayuth, R; Chierakul, W; White, N; Newton, P; Lubell, Y (BioMed Central, 2014)
BACKGROUND: Despite demonstrated benefits and World Health Organization (WHO) endorsement, parenteral artesunate is the recommended treatment for patients with severe Plasmodium falciparum malaria in only one fifth of endemic countries. One possible reason for this slow uptake is that a treatment course of parenteral artesunate is costlier than quinine and might, therefore, pose a substantial economic burden to health care systems. This analysis presents a detailed account of the resources used in treating falciparum malaria by either parenteral artesunate or quinine in a hospital on the Thai-Myanmar border. METHODS: The analysis used data from four studies, with random allocation of inpatients with falciparum malaria to treatment with parenteral artesunate or quinine, conducted in Mae Sot Hospital, Thailand from 1995 to 2001. Detailed resource use data were collected during admission and unit costs from the 2008 hospital price list were applied to these. Total admission costs were broken down into five categories: 1) medication; 2) intravenous fluids; 3) disposables; 4) laboratory tests; and 5) services. RESULTS: While the medication costs were higher for patients treated with artesunate, total admission costs were similar in those treated with quinine, US$ 243 (95% CI: 167.5-349.7) and in those treated with artesunate US$ 190 (95% CI: 131.0-263.2) (P=0.375). For cases classified as severe malaria (59%), the total cost of admission was US$ 298 (95% CI: 203.6-438.7) in the quinine group as compared with US$ 284 (95% CI: 181.3-407) in the artesunate group (P=0.869). CONCLUSION: This analysis finds no evidence for a difference in total admission costs for malaria inpatients treated with artesunate as compared with quinine. Assuming this is generalizable to other settings, the higher cost of a course of artesunate should not be considered a barrier for its implementation in the treatment of malaria.